Computed Energetics of Nucleotides in Spatial Ribozyme Structures: An Accurate Identification of Functional Regions from Structure - Ivan Y. Torshin (The Scientific World Journal)
Ribozymes are functionally diverse RNA molecules with intrinsic catalytic activity. Multiple structural and biochemical studies are required to establish which nucleotide bases are involved in the catalysis. The relative energetic properties of the nucleotide bases have been analyzed in a set of the known ribozyme structures. It was found that many of the known catalytic nucleotides can be identified using only the structure without any additional biochemical data. The results of the calculations compare well with the available biochemical data on RNA stability. Extensive in silico mutagenesis suggests that most of the nucleotides in ribozymes stabilize the RNA. The calculations show that relative contribution of the catalytic bases to RNA stability observably differs from contributions of the noncatalytic bases. Distinction between the concepts of “relative stability” and “mutational stability” is suggested. As results of prediction for several models of ribozymes appear to be in agreement with the published data on the potential active site regions, the method can potentially be used for prediction of functional nucleotides from nucleic sequence.